Comparison of Microleakage of MTA and CEM Cement Apical Plugs in Three Different Media - Ayatollahi, Fatemeh; Tabrizizadeh, Mahdi; Hazeri Baqdad Abad, Milad; Ayatollahi, Reza; Zare bidoki, Fatemeh (Iranian Endodontic Journal, 2016)
Introduction: Microleakage is of the causes of endodontic treatment failure. The aim of this in vitro study, was to compare the microleakage of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement apical plugs in three environments. Methods and Materials: A total of 130 human extracted single rooted teeth were collected. After decoronation, preparation of the root canal space and simulation of open apices, 5 teeth were selected as positive and negative control groups and the rest of the samples were randomly divided into two groups (MTA plug and CEM cement plug) and each group was divided into 3 subgroups (dry, contaminated with saliva and contaminated with blood). In each group apical plug was placed into the canal. After full setting of the apical plug, microleakage of the samples were evaluated using fluid filtration method and the data were analyzed using two-way analysis of variance. Results: In dry and saliva contaminated environments, the leakage of MTA samples were 40.906±2.081 and 39.608±2.081, respectively which was significantly more than that of CEM cement samples (26.977±2.081 and 27.000±2.081, respectively). However, in blood-contaminated environments, the amount of leakage in MTA group (21.640±2.081) was significantly lower than CEM cement group (44.358±2.081). Conclusion: According to the results of this study, in dry and saliva-contaminated conditions CEM cement provides significantly better seal in comparison to MTA. Keywords: Calcium-Enriched Mixture Cement; Microleakage; Mineral Trioxide Aggregate